Market Evidence on Investor Preference for Fewer Directorships - Bar-Hava, Keren; Gu, Feng; Lev, Baruch (Journal of Financial and Quantitative Analysis, 2020)
We examine investors’ preference for directors serving on fewer versus more boards (“busy directors”) by measuring market reaction to busy directors’ resignations at the companies that still keep these directors on the board. We find a positive reaction implying a preference for fewer directorships. The reaction is more positive when the need for the director’s services is greater, when the resignation frees up more of the director’s time, and when the director is of higher quality. Furthermore, we find that following their resignation, directors increase their board responsibilities/leadership at firms that still retain them and seek no board appointments elsewhere.